2010
DOI: 10.1016/j.actbio.2009.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Development of bioactive peptide amphiphiles for therapeutic cell delivery

Abstract: There is great clinical interest in cell-based therapies for ischemic tissue repair in cardiovascular disease. However, the regenerative potential of these therapies is limited due to poor cell viability and minimal retention following application. We report here the development of bioactive peptide amphiphile nanofibers displaying the fibronectin-derived RGDS cell adhesion epitope as a scaffold for therapeutic delivery of bone marrow derived stem and progenitor cells. When grown on flat substrates, a binary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
253
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(255 citation statements)
references
References 52 publications
(52 reference statements)
2
253
0
Order By: Relevance
“…These nanofibers have dimensions similar to filamentous structures in the extracellular matrix and can form gel networks at low concentrations in aqueous media, allowing for threedimensional entrapment of cells presuspended in aqueous PA solutions (13). Their high aspect ratio and the high surface area of displayed signals at controlled density likely facilitate their enhanced biological signaling, while their extensive internal hydration also offers the necessary dynamics to promote interaction with receptors and ligands (14)(15)(16).…”
mentioning
confidence: 99%
“…These nanofibers have dimensions similar to filamentous structures in the extracellular matrix and can form gel networks at low concentrations in aqueous media, allowing for threedimensional entrapment of cells presuspended in aqueous PA solutions (13). Their high aspect ratio and the high surface area of displayed signals at controlled density likely facilitate their enhanced biological signaling, while their extensive internal hydration also offers the necessary dynamics to promote interaction with receptors and ligands (14)(15)(16).…”
mentioning
confidence: 99%
“…Samples were prepared as described elsewhere 27 . Briefly, capsules were lyophilized and Olympus, Japan).…”
Section: Cell Proliferationmentioning
confidence: 99%
“…8,27,28 It has been shown that selfassembling peptide gels present a nanofibrillar network that resemble de structural architecture of extracellular matrix, making them attractive for studying cell-matrix interactions on a 3D environment. [29][30][31] Electrostatic-driven self-assembly between PAs of opposite charge was demonstrated by the formation of nanofibers with subsequent formation of self-supporting gels.…”
mentioning
confidence: 99%
“…For example, RAD16-II peptide gels stimulated angiogenesis of encapsulated human micro-vascular endothelial cells, 235 while studies of RAD16-I hydrogels showed them to support the growth and differentiation of encapsulated neuronal stem cells 236,237 and hepatocyte progenitor cells. 238 Hydrogels of alkyl-tail PAs functionalised with RGDS or IKVAV recognition sequences supported the proliferation of encapsulated bone marrow derived stem cells 221 or mouse neural progenitor cells 55 respectively. In separate studies, hydrogels of MAX8 supported the growth of encapsulated primary bovine chondrocytes.…”
Section: Cell Scaffoldsmentioning
confidence: 99%
“…However, it is possible to overcome this by incorporating a proportion of non-functionalised assembling peptide. 219,221,222,226,228 The optimal proportion of nonfunctionalised peptide is a factor that is expected to be sequence dependent and will likely need to be optimised empirically for each self-assembly peptide and functional motif.…”
Section: Cell Scaffoldsmentioning
confidence: 99%